A review on recent research results on bio-effects of plant essential oils against major Coleopteran insect pests. (June 2015) - Ebadollahi, Asgar; Jalali Sendi, Jalal
Abstract Upfront problems about the use of synthetic insecticides such as damage to the environment and human health and pests' resistance have brought about interest in natural compounds. In the last few years, more studies have been published for the insecticidal effects of essential oils from several plant families such as Apiaceae, Asteraceae, Cupressaceae, Lamiaceae, Lauraceae, Myrtaceae, Poaceae, Piperaceae, Rutaceae and Zingiberaceae. The present article emphases on the effects of essential oils against Coleopteran insect pests by highlighting on their extraction, chemical insecticidal properties, mode of action on insect, commercialization and safety.